A resiliência no processo de formação continuada dos professores e alunos - professores do curso de mestrado profissional em Ensino de Ciências na Amazônia - Belmont, Edileuza Maria Lima (2009)
The Resiliency in the Process of Continued Formation for Teachers and Students-Teachers of the Professional Master's Degree in Sciences Teaching in the Amazon is the title of this dissertation is the result of our research in order to investigate what kind of treatment is given by the Resiliency teachers and students-teachers in professional master's degree in Sciences Teaching in the Amazon. Therefore, we formulated the following specific objectives: To review the emerging approaches on Resiliency in the current literature, observe, perceive and describe on the Resiliency from the everyday actions of Teachers and Students-Teachers of the Professional Master's Degree in Sciences Teaching in the Amazon; Build a tool that allows to identify and discuss the sense, the meaning and Constitutive Factors of Resiliency, identify and promote this capacity in Teachers and Students-Teachers of Continued Formation courses in Sciences Teaching in the Amazon. The theoretical claims in authors such as: Flach (1991), Tavares (2002), Grotberg (2005), Miller (2006), Barbosa (2006), Poletti; Dobbs (2007), Delizoicov et al. (2002), Carvalho; Gil-Pérez (2006), Ghedin (2003), Frankl (2008) among others. The methodological procedures were guided by focus Humanist-Existential-Phenomenological and ethnographic methodology, with qualitative analysis as a way of description and interpretation of data collected. The result of the research allowed us to realize that the treatment given by the Resiliency Most teachers and student teachers is that they know and understand the meaning and significance of Resiliency, and forge meaningful links on this phenomenon and its constituent factors in both situations of their personal lives and in the professional, which led most important research subjects to consider the implementation of the study of Resiliency in the process of continuous training of teachers to help overcome difficulties ranging from relational to more specific exercise practice lecturer in Sciences Teaching.